2023
DOI: 10.1186/s12879-023-08468-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nontuberculous mycobacteria infections among persons with cystic fibrosis in the United States (2010–2019)

Abstract: Background Nontuberculous mycobacteria (NTM) are ubiquitous, environmental bacteria that can cause chronic lung disease. Persons with cystic fibrosis (pwCF) are at high risk for NTM. Approximately 1 in 5 pwCF in the United States (U.S.) is affected by pathogenic NTM species, and incidence rates of NTM have been increasing among pwCF as well as in the general population. Prevalence of NTM pulmonary infections (PI) varies widely across the United States because of geographic variation in environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This study identified the East South Central Region (included in the Southeast) and the Northeast as having the highest proportion of positive MAC cultures in the U.S. [ 24 ]. This is consistent with our prior study, which found the Northeast had the highest burden of MAC in the cystic fibrosis population [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study identified the East South Central Region (included in the Southeast) and the Northeast as having the highest proportion of positive MAC cultures in the U.S. [ 24 ]. This is consistent with our prior study, which found the Northeast had the highest burden of MAC in the cystic fibrosis population [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Exposure to pathogenic NTM species occurs primarily through drinking water, soil, and aerosols [ 1 ]. NTM risk and species-specific trends vary across the United States (U.S.) [ 4 7 ], but overall infection and disease incidence and prevalence are increasing in the United States [ 3 , 8 ]. This geographic variation is associated with differences in environmental factors [ 7 , 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global incidence rate of non-tuberculous mycobacteria (NTM) pulmonary disease has been increasing rapidly ( 1 , 2 ). In the United States, the infection rate and prevalence of NTM exceed those of tuberculosis (TB) ( 3-5 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Hospitalizations from NTM, P. aeruginosa, and L. pneumophila account for 44%, 13%, and 9%, respectively, of waterborne infection hospitalizations in the U.S., and NTM is responsible for the greatest percentage of total deaths, 57% (note: these numbers are underestimated due to underreporting of actual infections emerging from the reporting process). 6 Despite a range in existing disinfection regimens, 5 there remains a growing number of reports attributing waterborne infectious disease outbreaks to DWPIs [7][8][9] with the incidence of legionellosis 7 and NTM 8 pulmonary diseases continuing to increase in the USA. As a result, L. pneumophila, Mycobacterium avium, Mycobacterium abscessus, and P. aeruginosa are on the current U.S. EPA's contaminant candidate list.…”
Section: Introductionmentioning
confidence: 99%